How are metaphors rendered in legal translation? A corpus-based study of the European Court of Human Rights judgments - Božović, Petar (The Journal of Specialised Translation, 2022)
Rendition of metaphors from source to target linguaculture has been labelled as one of the most challenging translation tasks. As a pervasive feature of legal language which reflects and shapes the perception of law, metaphors have attracted the attention of numerous legal scholars. Surprisingly, however, the studies of metaphors in legal translation are still scarce. The present paper aims to contribute to this understudied area by attempting to shed light on how metaphors are rendered in translations of the ECtHR judgments and the underlying reasons for the choice of the translation strategy. To this end, I have scrutinised a corpus of 60 judgments in English and their translations into Montenegrin contained in the HUDOC repository. The results suggest that most of the metaphors used in the ECtHR judgments are lexicalised, dead metaphors and rendered via image transfer with a meagre omission rate suggesting that they are a prominent feature of both the source and target text and that there is a shared cognitive ground between the concerned LSPs. Monocultural metaphors trigger a varied translation behaviour as more strategies are employed. Transculturality seems to be one of the key influencing factors for the choice of a strategy. Finally, illustrative examples of the renditions of metaphors used for law, court, court procedure, rights, discrimination, truth and injustice are discussed.